Effectiveness of Internet-Based Group Supportive Psychotherapy on Psychic and Somatic Symptoms, Neutrophil-Lymphocyte Ratio, and Heart Rate Variability in Post COVID-19 Syndrome Patients - Hamzah Shatri; Dika Iyona Sinulingga; Cleopas Martin Rumende; Siti Setiati; Rudi Putranto; Eka Ginanjar; Iris Rengganis; Em Yunir; Raden Irawati Ismail; Petrin Redayani Lukman (Acta Medica Indonesiana, 2024)
Background: COVID-19 can have serious long term health consequences, which is called Post-COVID-19 Syndrome (PCS). Currently, the available evidence and understanding of PCS management is limited. Because one of the symptoms of PCS is associated to psychological symptoms, psychotherapy is believed to have a role in the management of PCS. This study aimed to identify the effectiveness of supportive psychotherapy in PCS patients at Cipto Mangunkusumo National General Hospital. Methods: This study was a single blind randomized clinical trial using a pre-and post-test with control group study design. Participants were randomly divided into two groups: a psychotherapy group with 40 participants and an education group with 37 participants. Each group was given internet-based psychotherapy or education three times a week in a form of group consisting of 6-8 participants. Symptom Checklist-90 questionnaire was used to evaluate somatic and psychological symptoms. Heart rate variability and neutrophil lymphocyte ratio were also investigated. Data analysis was performed using the independent T test. Results: An improvement in the SCL-90 score was found to be 17.51 (SD 30.52) in the psychotherapy group and 19.79 (SD 35.10) in the education group, although there was no significant difference between the two groups (p = 0.771). There was no significant difference between the two groups in decreasing NLR (p = 0.178) and improving HRV (p = 0.560). Conclusion: Both internet-based group supportive psychotherapy and education improved psychological and somatic symptoms in PCS patients, although there was no significant difference between the two groups. There was no significant difference between the two groups in decreasing NLR and improving HRV. Suggestions for further research regarding adding frequency of internet-based group psychotherapy in PCS patients and held in the morning to achieve more optimal results.